2015
DOI: 10.3892/ol.2015.3922
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 2 expression mediates cell proliferation and is associated with poor prognosis in human non-small cell lung carcinoma

Abstract: Abstract. Activating transcription factor 2 (ATF2) is a member of the cAMP response element binding protein family that heterodimerizes and activates other transcription factors involved in stress and DNA damage responses, growth, differentiation and apoptosis. ATF2 has been investigated as a potential carcinogenic biomarker in certain types of cancer, such as melanoma. However, its function and clinical significance in non-small cell lung cancer (NSCLC) has not been well studied. Therefore, the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…ATF2 is highly expressed in non small cell lung cancer and renal cell carcinoma, and is associated with the poor outcomes (Wu and Chen, 2016;You and Zhou, 2016). Our data showed that ATF2 was highly expressed in the pancreatic cancer tissues.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…ATF2 is highly expressed in non small cell lung cancer and renal cell carcinoma, and is associated with the poor outcomes (Wu and Chen, 2016;You and Zhou, 2016). Our data showed that ATF2 was highly expressed in the pancreatic cancer tissues.…”
Section: Discussionmentioning
confidence: 58%
“…ATF2 is highly expressed in non small cell lung cancer and renal cell carcinoma, and is associated with the poor outcomes (Wu and Chen, 2016;You and Zhou, 2016). Our clinical data showed that the expression of ATF2 in the tumor tissues of pancreatic cancer was higher than that in the adjacent non-tumor tissues, which prompted us to the hypothesis that ATF2 may play an oncogenic role in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Evidence suggests that ATF2 is imbalanced in individuals with cancer, whereas complete loss of ATF2 in somatic cells leads to cell death [39,41,42]. ATF2 is overexpressed in non-small cell lung cancer cells [43], and studies have shown that ATF2 increases the resistance of nonsmall cell lung cancer to cisplatin and radiotherapy by repairing DNA [44,45].…”
Section: Discussionmentioning
confidence: 99%